Inquiries into the Biological Significance of Transmembrane AMPA Receptor Regulatory Protein (TARP) γ−8 Through Investigations of TARP γ−8 Null Mice§ - D. Gleason, Scott; Kato, Akihiko; H. Bui, Hai; K. Thompson, Linda; N. Valli, Sabrina; V. Stutz, Patrick; Kuo, Ming-Shang; F. Falcone, Julie; H. Anderson, Wesley; Li, Xia; M. Witkin, Jeffrey (CNS & Neurological Disorders - Drug Targets, 2015)
Transmembrane AMPA (α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid) receptor regulatory protein (TARP) γ−8 is an auxiliary protein associated with some AMPA receptors. Most strikingly, AMPA receptors associated with this TARP have a relatively high localization in the hippocampus. TARP γ−8 also modifies the pharmacology and trafficking of AMPA receptors. However, to date there is little understanding of the biological significance of this auxiliary protein. In the present set of studies we provide a characterization of the differential pharmacology and behavioral consequences of deletion of TARP γ−8 by comparing the wild type (WT) and γ−8 -/- (knock-out, KO) mouse. KO mice were mildly hyperactive in a locomotor arena but not in other environments compared to WT mice. Additionally, the KO mice demonstrated enhanced locomotor stimulatory effects of both d-amphetamine and phencyclidine. Marble-burying and digging behaviors were dramatically reduced in KO mice. In another assay that can detect anxiety-like phenotypes, the elevated plus maze, no differences were observed in overall movement or open arm entries. In the forced-swim assay, KO mice displayed decreases in immobility time like the antidepressant imipramine and the AMPA receptor potentiator, LY392098. In KO mice, the antidepressant-like effects of LY392098 were prevented whereas the effects of imipramine were unaffected. Convulsions were induced by pentylenetetrazole, N-methyl-D-aspartate, and by kainic acid. However, in KO mice, kainic acid produced less tonic convulsions and lethality. KO mice had reduced levels of norepinephrine in hippocampus and cerebellum but not in hypothalamus or prefrontal cortex, decreased levels of cAMP in hippocampus, and increased levels of acetylcholine in the hypothalamus and prefrontal cortex. KO mice displayed decreased turnover of dopamine and increased histamine turnover in multiple brain areas In contrast, serotonin and its metabolites were not significantly affected by deletion of the γ−8 protein. Of a large panel of plasma lipids, only two monoacylglycerols (1OG and 2OG) were marginally but nonsignificantly altered in WT vs KO mice. Overall, the data suggest genetic inactivation of this specific population of AMPA receptors results in modest changes in behavior characterized by a mild hyperactivity which is condition dependent and a marked reduction in digging and burying behaviors. Despite deletion of TARP γ−8, chemoconvulsants were still active. Consistent with their predicted pharmacological actions, the convulsant effects of kainate and the antidepressant-like effects of an AMPA receptor potentiator (both acting upon AMPA receptors) were reduced or absent in KO mice.
Keywords: convulsions